Morphological characterization and hybridity confirmation of low chill peach (Prunus persica) hybrids using SSR markers - DEVI, INDIRA; SINGH, HARMINDER; THAKUR, ANIRUDH (The Indian Journal of Agricultural Sciences, 2018)
A hybridization programme was conducted during 2015 and 2016 with the main objective to widen the varietal range of early ripening cultivars. Crosses were made between low chill peach [Prunus persica (L.) Batsch] cultivars, taking Shan-i-Punjab and Tropic Sweet as a female and crossed with Florda Prince, Flordaglo and Prabhat and crosses of Shan-i-Punjab x Florda Prince showed maximum fruit set (72.63%), whereas minimum fruit set was recorded in Tropic Sweet × Flordaglo (18.87%). Although in Tropic Sweet crosses, fruit set was lower but they showed significantly higher percentage of fruit retention and lower percentage of fruit drop than the crosses made with Shan-i-Punjab cultivar. After ripening seeds were extracted from the fruits and were kept at low temperature for stratification until the seeds showed radicle emergence. Crosses made between Tropic Sweet × Flordaglo took maximum days for stratification (88.33). After sowing in the field maximum percentage of seed germination 90.43% was recorded in Tropic Sweet × Florda Prince seeds and maximum seedling height in Tropic Sweet × Flordaglo (36.03 cm). Very less variations were recorded among different crosses for petiole length and intermodal length and more rosetting was observed in Tropic Sweet hybrids. Among 22 SSR markers only six markers (MA015a, MA020a, MA023a, CPPCT-022, CPPCT-030 and UDP96-005) were able to test the hybridity of F1 seedling.